2016
DOI: 10.1212/wnl.0000000000002445
|View full text |Cite
|
Sign up to set email alerts
|

Results from a phase 1 study of nusinersen (ISIS-SMN Rx ) in children with spinal muscular atrophy

Abstract: Objective:To examine safety, tolerability, pharmacokinetics, and preliminary clinical efficacy of intrathecal nusinersen (previously ISIS-SMNRx), an antisense oligonucleotide designed to alter splicing of SMN2 mRNA, in patients with childhood spinal muscular atrophy (SMA).Methods:Nusinersen was delivered by intrathecal injection to medically stable patients with type 2 and type 3 SMA aged 2–14 years in an open-label phase 1 study and its long-term extension. Four ascending single-dose levels (1, 3, 6, and 9 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
437
0
19

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 546 publications
(477 citation statements)
references
References 25 publications
7
437
0
19
Order By: Relevance
“…Nusinersen (Spinraza, Biogen, Cambridge, MA, USA) has shown promising results in preclinical, early phase human, and clinical trials (47,57,58). The route of administration is intrathecal due to its poor transport across the blood-brain barrier.…”
Section: Antisense Oligonucleotidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nusinersen (Spinraza, Biogen, Cambridge, MA, USA) has shown promising results in preclinical, early phase human, and clinical trials (47,57,58). The route of administration is intrathecal due to its poor transport across the blood-brain barrier.…”
Section: Antisense Oligonucleotidesmentioning
confidence: 99%
“…Therefore, increasing SMN protein level is the most straightforward approach for SMA therapy, and has been studied for years with different strategies such as correction of SMN2 splicing, modulation of SMN gene expression, prevention of protein degradation, and replacement of SMN1 (reviewed in 3,33-37). Significant efforts have been made to develop or identify effective small molecules (38)(39)(40)(41)(42)(43)(44), antisense oligonucleotides (45)(46)(47), and viral vectors (48)(49)(50) in order to increase SMN in preclinical research. The efficacy of some of the above has been tested in clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…The AEs most frequently reported by study participants following treatment with nusinersen were headache (39.3%), post-lumbar puncture headache (21.4%), and back pain (17.9%). While the most common side effects of nusinersen are respiratory infections and constipation, the FDA has also issued warnings with respect to the possibility of thrombocytopenia and renal toxicity [75,76].…”
Section: Nusinersen (Spinraza)mentioning
confidence: 99%
“…84 Recently, antisense drugs designed to alter splicing have entered human clinical trials and have shown signs of clinical activity in various disease settings, with the most compelling and clear demonstration of ASO-mediated splice modulation in man coming from the robust demonstration of clinical proof of mechanism with Isis SMN RX (nusinersen), where intrathecal administration of the splice-modulating ASO to children afflicted with SMA led to time-and dose-dependent increases in several muscle function parameters. 85,86 Very recently, nusinersen, has unequivocally demonstrated that this approach is viable and can deliver significant clinical benefit in infants afflicted with SMA. 87 Importantly for SMA patients, an interim analysis of the phase 3 placebo-controlled clinical of nusinersen in this patient population demonstrated highly significant positive effects, and nusinersen (Spinraza) has now been approved by the Food and Drug Administration for the treatment of all patients with SMA.…”
Section: Splice Modulating Asosmentioning
confidence: 99%